Selected Abstracts of the 1st Congress of joint European Neonatal Societies (jENS 2015); Budapest (Hungary); September 16-20, 2015; Session "Ethics and limitations to care" - - (Hygeia Press di Corridori Marinella, 2015)
Selected Abstracts of the 1st Congress of joint European Neonatal Societies (jENS 2015); Budapest (Hungary); September 16-20, 2015 ORGANIZING INSTITUTIONS European Society for Neonatology (ESN), European Society for Paediatric Research (ESPR), Union of European Neonatal & Perinatal Societies (UENPS), European Foundation for the Care of Newborn Infants (EFCNI), with the local host of Hungarian Society of Perinatology and Obstetric Anesthesiology, Hungarian Society of Perinatology (MPT), supported by Council of International Neonatal Nurses (COINN), organizing secretariat MCA Scientific Events PROGRAMME COMMITTEE Artúr Beke (Hungarian Society), Morten Breindahl (ESN), Giuseppe Buonocore (UENPS), Pierre Gressens (ESPR), Silke Mader (EFCNI), Manuel Sánchez Luna (UENPS), Miklós Szabó (Hungarian Society of Perinatology), Luc Zimmermann (ESPR)   Session "Ethics and limitations to care" ABS 1. METHODS TO DERIVE UTILITIES FOR PEDIATRIC DISABILITY IN A DEVELOPING COUNTRY • E. Spiegel, I. Brajkovic, S. Jondhale, J. Partridge, V. Bhutani, P. Kumar ABS 2.UTILITIES FOR DISABILITY IN A DEVELOPING COUNTRY: PROVIDER PERSPECTIVES • S. Jondhale, E. Spiegel, I. Brajkovic, J. Partridge, V. Bhutani, P. Kumar ABS 3.LIMITING LIFE SUSTAINING TREATMENT FOR NEWBORN INFANTS: THE WILST STUDY • N. Aladangady, C. Shaw, K. Gallagher, E. Stokoe, N. Marlow for Collaborator Group ABS 4.NEONATAL ORGAN DONATION IN SCOTLAND • L. Leven, N. Healy, K. O'Reilly ABS 5.GLOBAL PREVENTION OF Rh-SENSITIZATION: AN INTERACTIVE, COMMUNITY-CENTERED SOCIAL PLATFORM • A.R. Stark, J.Y. Hall, A. Zipursky, V.K. Bhutani